The Golden Age of Nobel Economists - Hendrik P. van Dalen (Tinbergen Institute, 1997)
Nobel laureates in economics make their most important and creative contributionsbetween the ages of 29 and 38. The average creative age of Nobel economists is slightly belowthat of laureates in physics, and considerably younger than that of laureates in chemistry andmedicine/physiology. The University of Chicago and the US in general has so far turned outto be best breeding ground for original economists. Furthermore,most fundamental work has been written alone and this finding contrasts strongly with thedominant trend in economics where multi-authored papers_new have become the rule inpublishing.
Keywords: A11; J24; J44; 330; Age; economists; Nobel Prize; productivity; Preisverleihung; Wissenschaftliches Arbeiten; Altersgruppe; Welt